Agricultural Policy: A Driver for Structural and Technological Change - Martinho, Vítor (2022)
This book gives insights into the agricultural policies in several countries located in different continents. It is of interest to students, researchers, and policy and decision makers. Given the particularities of agriculture, agricultural policies are indispensable for an adjusted development of farms according to the strategic objectives of each country, namely the socio-economic and environmental ones. The question that often arises is whether the practical effects of the various policy measures are in accordance with their design and what is the effect of these policy instruments among many other causes of structural and technological change. The aim of this book is to describe the main agricultural policies that have been implemented in countries such as the United States of America, Brazil, China, India, South Africa, Australia, as well as the European Union. It also aims to analyse the real impact of these policies on the structural and technological changes of farms in the European Union. As its methodology, the book considers bibliometric analysis, literature review and statistical approaches.